Review of Food Estate Legal Policy in Maintaining Food Sovereignty Based on State Obligations - Laga Sugiarto; Ishaq Dhimas Bayuaji (Universitas Negeri Semarang, 2026)
This study analyzes the legal framework of Indonesia's Food Estate policy, evaluating its alignment with the constitutional mandate of Food Sovereignty and State Obligations. Employing normative legal research with Regulatory Impact Assessment (RIA) and ROCCIPI frameworks, the study diagnoses regulatory disharmony and effectiveness. The findings reveal a fundamental paradigm shift from